PENGARUH KREDIT BERMASALAH, SIMPANAN ANGGOTA DAN JUMLAH ANGGOTA TERHADAP SISA HASIL USAHA (SHU) PADA KOPERASI SIMPAN PINJAM SINAR HARAPAN JEREBUU - Ririn, Maria Oktavia Klaudia; Banda, Falentina Lucia; Londa, Yulita (Program Studi Akuntansi Universitas Flores, 2023)
The purpose of this study is to determine the effect of non-performing loans, member savings and the number of members on the remaining operating results (SHU) in the Sinar Harapan Jerebuu Savings and Loans Cooperative. This type of research used is quantitative research. The data used is secondary data which is the financial report data of Savings and Loan Cooperatives The results showed that: 1) The number of non-performing loans has a negative effect on the amount of Remaining Business Results (SHU) in the Sinar Harapan Jerebuu Cooperative. This is evidenced by the value of tcount > ttable (-2.356 > 2.00324) and a significant level of 0.006 <0.05. This means that as the increasing number of non-performing loans, the total remaining business results (SHU) at the Sinar Harapan Jerebuu Savings and Loans Cooperative will increasingly experience an decrease in profits for the company in accordance with the reduced number of bad loans. 2) Total Member Savings has a positive effect on Total Remaining Results of Operations (SHU) at the Sinar Harapan Jerebuu Savings and Loans Cooperative. This is evidenced by the value of tcount > ttable (2.943 > 2.00324) and a significant level of 0.001 <0.05. This means that the number of members' savings increases, so the amount of remaining business results (SHU) at the Sinar Harapan Jerebuu Savings and Loans Cooperative is getting better and increasing or getting bigger. 3) The number of members has a positive effect on the amount of remaining business results (SHU) at the Sinar Harapan Jerebuu Savings and Loans Cooperative. This is evidenced by the value of tcount > ttable (2.389 > 2.00324) and a significant level of 0.020 <0.05. This means that the increase in the number of members means that the amount of remaining business results (SHU) received by the Sinar Harapan Jerebuu Savings and Loans Cooperative also increases in accordance with the increase in the number of members.